A severe course of serogroup W meningococcemia in a patient with infantile nephropathic cystinosis - Gurkan Bozan; Omer Kilic; Nuran Çetin; Gonca Kılıç Yıldırım; Hasan Bora Ulukapi; Merve Iseri Nepesov; Aslı Kavaz Tufan; Ener Cagri Dinleyici (Human Vaccines & Immunotherapeutics, 2020)
We present a 9-month old boy with cystinosis admitted to our hospital with the complaints of vomiting, diarrhea and seizure. While he was hospitalized in a pediatric intensive care unit due to worsening of his signs related to cystinosis, within hours, he suffered complications of septic shock, acute renal failure, and disseminated intravascular coagulation, due to invasive Neisseria meningitidis serogroup W disease. Our patient is the first reported case of invasive meningococcal disease with cystinosis. Clinicians should consider that the unexpected and serious clinical findings of invasive meningococcal disease can mimic and/or masquerade as other metabolic diseases. Vaccination strategies, according to serogroup epidemiology and age distribution, should be implemented for the prevention of meningococcal infections.